2017
DOI: 10.1021/acs.est.7b03567
|View full text |Cite
|
Sign up to set email alerts
|

Ingestion of Microplastics by Freshwater Tubifex Worms

Abstract: Microplastic contamination of the aquatic environment is a global issue. Microplastics can be ingested by organisms leading to negative physiological impacts. The ingestion of microplastics by freshwater invertebrates has not been reported outside the laboratory. Here we demonstrate the ingestion of microplastic particles by Tubifex tubifex from bottom sediments in a major urban waterbody fed by the River Irwell, Manchester, UK. The host sediments had microplastic concentrations ranging from 56 to 2543 particl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
123
2
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(138 citation statements)
references
References 75 publications
8
123
2
5
Order By: Relevance
“…MP ingestion has been previously demonstrated for Tubifex worms, which belong to the family Naididae (24). In a study by Hurley et al (24), Tubifex worms were able to ingest MP fragments with a size between 50 and 4500 m contained in natural sediment and were found to retain MP for longer time periods than other sediment components. A reduction in food intake due to the dilution of organic matter in the sediment, together with the uptake and longer retention of MP by the Naididae worms, could have caused a depletion of energy reserves over time, as previously found in laboratory tests for other benthic invertebrates (6,9,25).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…MP ingestion has been previously demonstrated for Tubifex worms, which belong to the family Naididae (24). In a study by Hurley et al (24), Tubifex worms were able to ingest MP fragments with a size between 50 and 4500 m contained in natural sediment and were found to retain MP for longer time periods than other sediment components. A reduction in food intake due to the dilution of organic matter in the sediment, together with the uptake and longer retention of MP by the Naididae worms, could have caused a depletion of energy reserves over time, as previously found in laboratory tests for other benthic invertebrates (6,9,25).…”
Section: Discussionmentioning
confidence: 92%
“…Table S4. Temperature (°C), dissolved oxygen (mg/liter), pH, and electro-conductivity (S/cm) measured at two locations (meters 10 and 30) in the experimental ditch at the start of the experiment (0) and after 1,2,3,5,6,7,11,12,24,36,48, and 60 weeks. Fig.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…Consequentially, PVC and PET, which are materials for plastic sewers, tubes and beverage bottles (Oberbeckmann et al 2016), are often found in freshwater sediments (Ehlers et al 2019;Jiang et al 2019). Once in the sediment, MPs are encountered by benthic organisms and are often consumed (Hurley et al 2017;Mohsen et al 2019). Therefore, to date, most microplastic studies have investigated the oral uptake of microplastics by (epi)benthic animals (Redondo-Hasselerharm et al 2018;Courtene-Jones et al 2019;Windsor et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have confirmed the intake of microplastics by 39 freshwater species, including 4 species of fish and 35 species of invertebrate [32]. The average concentration of microplastics ingested by Tubifex tubifex exposed to sediments in urban UK was 129 ± 65.4 particles g −1 , mostly in form of fiber [33]. Microplastics were found in 61 of 63 Asian clam samples (2-4 clams per sample) a field investigation [34].…”
Section: Environmental Behaviormentioning
confidence: 77%